Գեղունի Չթչեանի մանկապատանեկան խմբերգային երաժշտութեան ժառանգութիւնը - Քէշիշեան, Զաքար (տպ. Atlas)
Armenian children’s բազմաձայն choir songs started in the second half of the 19th century. Its founders were Christapor Gara Murza, Magar Yegmalian, and Gomidas. Their legacy was further developed in both the Diaspora and Soviet Armenia in the 20th century to the extent that currently there are over 400 children’s choir songs in Armenian. Among the 20th century composers who dedicated a significant part of their energy to this genre, Keghuni Chetchian’s efforts are outstanding. By examining Chetchian’s compositions, the author highlights the characteristics of the composer’s children’s choir songs, brings forth a number of songs and their notes to underline Chetchian’s skillful combination of lyrics and music, as well as the wise matching of the musical instrument and the melody of the song, plus the musical effects which underpin the meanings of the script. Alongside the accompaniment features of her songs, the author notes that Chetchian’s compositions are not only in line with the Armenian heritage of children’s songs, but with the legacy of Armenian music composition in general.
Keywords: Երաժշտութիւն; Արուեստ